The Arabidopsis thaliana nucleotide sugar transporter GONST2 is a functional homolog of GONST1. (19th March 2021) - Jing, Beibei; Ishikawa, Toshiki; Soltis, Nicole; Inada, Noriko; Liang, Yan; Murawska, Gosia; Fang, Lin; Andeberhan, Fekadu; Pidatala, Ramana; Yu, Xiaolan; Baidoo, Edward; Kawai‐Yamada, Maki; et al.
Abstract: Glycosylinositolphosphorylceramides (GIPCs) are the predominant lipid in the outer leaflet of the plasma membrane. Characterized GIPC glycosylation mutants have severe or lethal plant phenotypes. However, the function of the glycosylation is unclear. Previously, we characterized Arabidopsis thaliana GONST1 and showed that it was a nucleotide sugar transporter which provides GDP‐mannose for GIPC glycosylation. gonst1 has a severe growth phenotype, as well as a constitutive defense response. Here, we characterize a mutant in GONST1's closest homolog, GONST2. The gonst2‐ 1 allele has a minor change to GIPC headgroup glycosylation. Like other reported GIPC glycosylation mutants, gonst1‐1gonst2‐1 has reduced cellulose, a cell wall polymer that is synthesized at the plasma membrane. The gonst2‐1 allele has increased resistance to a biotrophic pathogen Golovinomyces orontii but not the necrotrophic pathogen Botrytis cinerea . Expression of GONST2 under the GONST1 promoter can rescue the gonst1 phenotype, indicating that GONST2 has a similar function to GONST1 in providing GDP‐D‐Man for GIPC mannosylation.